Differentials and persistence in unemployment - an analysis of the Spanish regions with the highest unemployment rates - Ines Murillo; Fernando Nú\~nez; Carlos Usabiaga (European Regional Science Association (ERSA), 2005)
The objective of the present paper is to contribute to the study of the labour markets of two Spanish regions that have mantained over the last few decades a persistent unemployment differential with respect to the remainder of the country: Andalusia and Extremadura. To this end, a brief descriptive analysis is given of the most important variables of these regional labour makets, together with the corresponding shift-share and virtual economy analysis. To study the degree of persistence of the unemployment rate in these two regions, the behaviour of their labour markets in response to specific shocks in employment is examined by means of a VAR analysis, following the method proposed by Blanchard y Katz (1992). One of the most noteworthy aspects brought out by the descriptive analysis was that, although the labour markets of Andalusia and Extremadura share many characteristics - indeed most of those that were analyzed- they also present differenciated patterns of behaviour in some important variables. For example, in the case of Andalusia economy, there is a notably strong growth of the labor force. This contrasts whit the weakness of employment growth in the Extremadura economy. Also worthy of note is the greater wage flexibility in Extremadura compared to Andalusia. From the VAR analysis applied to each of these two regions, one can conclude that a specific demand shock in Andalusia and Extremadura has permanent effects on the participation rate - especially in Andalusia- and on the unemployment rate - especially in Extremadura-, with the migratory movements in these regions being too low to return these variables to the level they had prior to the demand shock. In sum, the present paper points to a set of factors that could contribute to explaining the unemployment differentials of Andalusia and Extremadura relative to the rest of Spain. More specific analyses would be required to evaluate the explanatory capacity of each of these factors in accordance with the underlying methodology and theories corresponding to each case.
Keywords: 330